To Explore Maybank's Stock Performance as the Top Stock Among Kuala Lumpur Stock Exchange (KLSE) in Bursa Malaysia - Dr Yeoh Wee Win (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The study had been focusing to investigate on the Maybank’s stock performance as the top stock among the Kuala Lumpur Stock Exchange (KLSE) in Bursa Malaysia. The study had been addressing two major research questions which include “How Maybank’s stock performance fare against the stock market performance in KLSE?” and “How is the perspective of the investors towards the stock of Maybank?”. The research questions had been derived from the motivation of the gap in the previous study where there is lacking study on the top stocks’ performance had induced the study to focus on the study to understand the performance of the Maybank stock investment as well as the perspective of the investors towards the top stock like Maybank. The quantitative study had been carried out with the series of the statistical output including the reliability test, correlation analysis and regression analysis as well as the application on the comparative analysis to explore the understanding between the KLSE market index and Maybank stock. The results had showed that Maybank stock performance tends to be higher against the performance of the market index in KLSE signaling that the Maybank as the top stock in Bursa Malaysia is consistently higher in the long-term but failed to pose any evidence in similar event in the short-term. On the other hand, the investors had been sharing the very similar confidence level towards the Maybank stock investment against the Bursa Malaysia which provide the indication that the investors are confidence with the Maybank’s stock performance based on the growth in the stock market in Bursa Malaysia..